Evaluation of the Clinical, Laboratory and Imaging Findings of Patients with COVID-19 and Their Associations with Clinical Outcomes in an Iranian Hospital: A Cross-Sectional Study - Tehrani, Shabnam; Yadegarinia, Davood; Abolghasemi, Sara; Sali, Shahnaz; Abrishami, Alireza; Moradi, Hamideh; Khabiri, Neda (Novelty in Biomedicine, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a concern in the medical community as the virus spreads around the world. It has a heavy global burden, particularly in low-income countries. This virus has its specific outcomes in each population. Hence, it is necessary to design studies to find the epidemiological behaviour of this virus. Materials and Methods: This cross-sectional study was conducted in the Labbafinezhad hospital, Tehran, Iran. Demographic features include age, sex, past medical history, drug history, habitual file, influenza vaccination history, recent exposure history, clinical symptoms or signs, and the recorded symptoms. The clinical examination and para-clinical assessment, including chest computed tomography (CT) and laboratory testing on admission, were recorded. Results: It was found that patients with a history of kidney transplantation, high level of LDH, high level of AST, and increased neutrophil to lymphocyte ratio are most at risk of death. Conclusion: Parameters mentioned could help practitioners predict patient outcomes, and necessary interventions could be considered in this regard.